2008
DOI: 10.1080/10550490802268835
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Buprenorphine and Methadone Among Opioid‐Dependent Individuals

Abstract: Attitudes and beliefs about drug abuse treatment have long been known to shape response to that treatment. Two major pharmacological alternatives are available for opioid dependence: methadone, which has been available for the past 40 years, and buprenorphine, a recently-introduced medication. This mixed methods study examined the attitudes of opioid-dependent individuals toward methadone and buprenorphine. A total of 195 participants (n = 140 who were enrolling in one of 6 Baltimore area methadone programs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 20 publications
(24 reference statements)
4
91
2
Order By: Relevance
“…Fewer participants in our sample mentioned buprenorphine than methadone but those who were aware of the medication (nearly always referred to it as generic "buprenorphine" rather than by a brand name) tended to have favorable attitudes towards it. (33) None of our study participants reported injecting methadone or buprenorphine. Methadone has rarely been abused by injection in the U.S. (15) although it has been reportedly injected in Australia and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer participants in our sample mentioned buprenorphine than methadone but those who were aware of the medication (nearly always referred to it as generic "buprenorphine" rather than by a brand name) tended to have favorable attitudes towards it. (33) None of our study participants reported injecting methadone or buprenorphine. Methadone has rarely been abused by injection in the U.S. (15) although it has been reportedly injected in Australia and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 515 heroin-addicted individuals from the Baltimore City area were recruited for the study, including 351 participants who were entering treatment at one of the six MTPs associated with the study and 164 participants who were neither enrolled in nor seeking treatment. (32,33) There were no statistically significant differences between the in-treatment and out-of-treatment participants in terms of their demographic characteristics (including age, gender, marital status), level of education, number of days employed, or route of heroin administration. (31) All participants received the surveys described below.…”
Section: Participantsmentioning
confidence: 99%
“…4 Methadone maintenance treatment slots are available for only 20% of opioid dependent persons, making linkage from correctional facilities to community methadone treatment even more challenging. 12 Buprenorphine/naloxone, a partial opioid agonist available for office-based treatment of opioid dependence since 2002, has important benefits for treating criminal justice populations, including heightened patient satisfaction and adherence, 13,14 reduced risk for misuse, 12 and perhaps, most importantly, the potential for initiation and maintenance in a primary care or office-based setting. To our knowledge, there are no data on the impact of patient history of incarceration on treatment outcomes of primary care office-based buprenorphine/naloxone.…”
mentioning
confidence: 99%
“…Examining how buprenorphine is viewed from the user's perspective -both as a pharmacological agent and as a service delivery model -is critical for understanding the decision processes underlying their treatment selection. Based on our previous research on treatment entry and engagement, [8][9][10][11][12][13][14][15][16][17][18][19] we hypothesized that patients would choose buprenorphine treatment due to its perceived advantages over methadone in patient burden (e.g. ability to receive takehome medication more quickly, fill prescriptions at a regular pharmacy, etc.).…”
Section: Introductionmentioning
confidence: 99%